A re-evaluation of the taphonomic methodology for the study of small mammal fossil assemblages of South America - Fernández, Fernando Julián (2017)
The taphonomic methodology for the study of small mammal fossil was based mainly on actualistic studies of bones and teeth of insectivores (Soricidae, Talpidae, Erinaceidae) and rodents (Arvicolinae, Muridae) recovered from pellets of birds of prey and scats of carnivorous mammals from different places of North America, Europe and Africa. The digestive corrosion patterns on teeth of the South American rodents Sigmodontinae, Caviinae, Ctenomyidae and Abrocomidae, and the marsupials Monodelphini of central Argentina were observed. The comparison between the South American samples with the North American, African and European samples allowed us to establish similarities and differences in the digestive corrosion of the teeth. The main agreements have been recorded in the following groups: Arvicolinae with Caviinae and Abrocomidae; Murinae with Sigmodontinae; Soricidae, Talpidae and Erinaceidae with Monodelphini. However, the particular and simplified configuration of the molars of Ctenomyidae with thicker enamel and dentine exposed has promoted a new description of the categories of digestive corrosion. Likewise Muridae and Sigmodontinae molars, Ctenomyidae presents a delay in the appearance of signs of digestion with regard to other caviomorphs (Caviinae, Abrocomidae). This contribution may, therefore, be useful to know the origin of these South American faunas and the exact taphonomic agent that produced these assemblages. Finally, small mammal samples from an archaeo-palaeontological site from Northwestern Patagonia, Argentina, were studied in order to apply the new methodology emerged from the recent samples.